"'I just don't ever use that word': investigating stakeholders' understanding of heritage". Issue 7 (9th August 2018) - Kryder-Reid, Elizabeth; Foutz, Jeremy W.; Wood, Elizabeth; Zimmerman, Larry J.
Abstract: Understanding the value of heritage sites for diverse stakeholders requires both paying attention to the fields of power in which the sites operate and applying methodologies that are open to user-defined paradigms of value. In the U.S., official discourse often frames the value of heritage sites associated the deep Native American past as archaeological sites, an interpretation that is consistent with settler colonial ideologies. This narrative generally obfuscates connections between the heritage of the sites and contemporary peoples, and it effaces the history of colonialism and dispossession. A study of stakeholder-defined heritage at two contested sites in the central Midwest revealed both congruencies and conflicts among diverse constituencies' articulations of the sites' value. At Mounds State Park a proposed dam and reservoir 'Mounds Lake' project would inundate a large portion of the site. At Strawtown Koteewi, Native American tribes have made repatriation claims under the federal Native American Graves Protection and Repatriation Act (NAGPRA).The study also problematised the term 'cultural heritage' as it is understood and used by the different constituencies, particularly for culturally and historically affiliated Native Americans. It also highlighted the positions of the constituencies within the broader fields of power implicated in these contested sites.